2014
DOI: 10.1002/jbm.a.35236
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell responses to nanotopography

Abstract: Cells interact with various nanoscaled topographical and biochemical cues in their cellular macromolecular environment. Nanotopography recreates or mimic the cellular macromolecular environment in vitro. The influence of material surface topography on the behavior of adherent cells has been studied. Current techniques enable various kinds of nanopatterned surface to be generated and applied to cells. The purpose of this review is to provide an overview of nanotopography and its surface patterns, and introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 62 publications
2
16
0
2
Order By: Relevance
“…We have previously demonstrated that BMPC growth was equivalent on tissue culture surfaces or PFVH‐CH‐B scaffold, suggesting that in the present study the differences in adhesion and proliferation may be influenced by surface characteristics rather than by the chemical nature of the scaffold. In agreement with these results, we and other groups have demonstrated that the topography of the substratum may influence cell attachment, proliferation and commitment . Moreover, surface characteristic influences also cell spreading and cytoskeleton rearrangement which in turn could influence the differentiation potential of BMPC …”
Section: Resultssupporting
confidence: 89%
“…We have previously demonstrated that BMPC growth was equivalent on tissue culture surfaces or PFVH‐CH‐B scaffold, suggesting that in the present study the differences in adhesion and proliferation may be influenced by surface characteristics rather than by the chemical nature of the scaffold. In agreement with these results, we and other groups have demonstrated that the topography of the substratum may influence cell attachment, proliferation and commitment . Moreover, surface characteristic influences also cell spreading and cytoskeleton rearrangement which in turn could influence the differentiation potential of BMPC …”
Section: Resultssupporting
confidence: 89%
“…The major effects of topography on cells are cell adhesion, proliferation, morphological changes, migration, and organization, which ultimately helps determine cell fate [65]. The ranges of topographical cues investigated span from the micro to the nano scale.…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…Some reports describe the relationship between the orientation of cell pseudopodia and nanostructure . However, there is still not a uniform conclusion to expound the mechanism of how the nano‐topographic structures have an effect on cells …”
Section: Resultsmentioning
confidence: 99%